Pelaksanaan Pelayanan Publik Bidang Administrasi di Kantor Kecamatan Batuwarno Kabupaten Wonogiri - Redyantoko Danang Prasetyo; Susantiningrum Susantiningrum; Hery Sawiji (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to analyze the implementation of public services in the administrative sector at the Batuwarno District Office, Wonogiri Regency. The research employed a descriptive qualitative approach. The data sources in this study include informants, research settings and events, as well as supporting documents. The sampling technique used was snowball sampling. Data were collected through three main methods: interviews, observations, and documentation studies. The validity of the data was tested using four criteria—credibility, confirmability, transferability, and dependability. Data analysis was carried out by applying the interactive analysis model. The results of the study indicate that: (1) the implementation of administrative services at the Batuwarno District Office has not yet been optimal, particularly in terms of facility maintenance and repair, which are essential to support efficient service delivery; (2) the main obstacles encountered include insufficient facility maintenance and a lack of understanding of administrative procedures among both the public and the staff; and (3) efforts undertaken to address these issues include improving coordination with related agencies, implementing the SAMBAT PAK CAMAT and DIK SUKMA programs, providing online administrative services, and distributing informational brochures and pamphlets on administrative services.